The continuing search for an addiction vaccine. Issue 36 (23rd August 2019) - Ozgen, M. Heval; Blume, Stuart
Abstract: Inspired by advances in immunology, in the 1970s scientists began to study the possibilities of mobilizing the human immune system against intruders other than pathogenic viruses and bacteria. In 1972 the suggestion was first made that it might be possible to provoke immunity to narcotic dependence. Because molecules of narcotics such as heroin and cocaine are too small to stimulate an immune response, researchers sought ways of coupling them to immunogenic proteins. The substances they developed soon became known as addiction vaccines. However, despite fifty years of research, and despite the growing problem of addiction, no vaccine against heroin, cocaine, methamphetamine or nicotine addiction has yet been licensed for clinical use. This paper reviews the history of addiction vaccinology, seeks to explain the unique appeal of a vaccinological approach to addiction, and argues for broad discussion of how such vaccines should ultimately be used.